2010
DOI: 10.1007/s10875-010-9440-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of NLRP3 Inflammasome Activation

Abstract: The inflammasome is an intracellular multimolecular complex that controls caspase-1 activity in the innate immune system. NLRP3, a member of the NLR family of cytosolic pattern recognition receptors, along with the adaptor protein ASC, mediates caspase-1 activation via assembly of the inflammasome in response to various pathogen-derived factors as well as danger-associated molecules. The active NLRP3 inflammasome drives innate immune response towards invading pathogens and cellular damage, and regulates adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
280
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(295 citation statements)
references
References 36 publications
4
280
0
2
Order By: Relevance
“…It was previously reported that intranasal administration of chitin beads induced infiltration of IL-4-expressing cells in lung, but administration of chitin beads that were pretreated with recombinant AMCase failed to induce infiltration of IL-4-expressing cells in lung (11). It was also reported that mice that expressed AMCase constitutively in lung demonstrated a significant reduction of eosinophil infiltration after administration of chitin beads or fungal challenge (11,35). These reports support our observations that enzymatically inactive AMCase-ED mice showed enhanced infiltration of eosinophils in lung and type 2 immune responses after administration of HDM or chitin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that intranasal administration of chitin beads induced infiltration of IL-4-expressing cells in lung, but administration of chitin beads that were pretreated with recombinant AMCase failed to induce infiltration of IL-4-expressing cells in lung (11). It was also reported that mice that expressed AMCase constitutively in lung demonstrated a significant reduction of eosinophil infiltration after administration of chitin beads or fungal challenge (11,35). These reports support our observations that enzymatically inactive AMCase-ED mice showed enhanced infiltration of eosinophils in lung and type 2 immune responses after administration of HDM or chitin.…”
Section: Discussionmentioning
confidence: 99%
“…The results support the following model. The enzymatically cleaved chitin is taken up by cells through phagocytosis, which then triggers activation of caspase-1 through this wellcharacterized pathway (35,36), whereas uncleaved chitin promotes the release of IL-33 probably due to mechanical damage to lung tissue. The activation of caspase-1 leads in turn to the activation of caspase-7, which inactivates IL-33, thereby resolving type 2 immune responses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DTA0118 significantly inhibited the synthesis of cytokines. IL-1β was generated presumably by activation of the inflammasome, 19 which has been linked to the pathogenesis of ARDS. 20 This inhibition of proinflammatory cytokines has also been …”
Section: Discussionmentioning
confidence: 99%
“…Iwata et al (2015) have found that exposure to acute immobilization stress (60 min) resulted in the intrahippocampal release of ATP concomitant with IL-1β protein as well as NLRP3 inflammasome activation. These effects of stress were prevented in a Nlrp3 KO mouse and were blocked by peripheral administration of an antagonist to the P2X7 receptor, which mediates ATP activation of the NLRP3 inflammasome (Jin and Flavell, 2010), suggesting that stress-induced release of ATP mediates NLRP3 inflammasome activation and subsequent release of IL-1β. Further, they found that chronic administration of a P2X7 receptor antagonist during exposure to CUS ameliorated several effects of stress on depressive-like behaviors including the sucrose preference test, the novelty suppressed feeding test, and elevated plus maze.…”
Section: Atpmentioning
confidence: 98%